Tracking Performance Achievement for Continuous‐Time Delayed Linear Systems Subject to Actuator Saturation and output Disturbances. Issue 5 (10th September 2014) - Mahjoub, Adel; Van Assche, Vincent; Giri, Fouad; Chaoui, Fatima Z.
Abstract Controlling continuous‐time input‐delayed nonminimum‐phase linear systems is addressed in the presence of actuator saturation and output‐disturbances. Focusing on output‐reference tracking, the control design is dealt with in the pseudo‐polynomials ring. A quite appealing L2 ‐tracking performance is shown to be achievable in the presence of arbitrary inputs i.e. the output reference and the output disturbance. The performance is formulated in terms of a well defined output‐reference mismatch error (ORME), depending on the inputs' rate and their compatibility with the actuator saturation constraint.